Renal Dysfunction is an Independent Risk Factor for Rebleeding After Endoscopic Hemostasis in Patients with Peptic Ulcer Bleeding - Hideharu Ogiyama; Shusaku Tsutsui; Yoko Murayama; Kensuke Matsushima; Shingo Maeda; Shin Satake; Kayo Seto; Masashi Horiki; Tamana Sanomura; Kazuho Imanaka; et al. (Turkish Journal of Gastroenterology, 2021)
Background: Despite the progress in endoscopic hemostasis and pharmacological treatment, the mortality rate of peptic ulcer bleeding remains at 5–10%. Rebleeding after peptic ulcer bleeding is believed to be a risk factor for mortality. This study aimed to evaluate whether renal dysfunction is a predictor of rebleeding after endoscopic hemostasis in patients with peptic ulcer bleeding. Methods: In this retrospective study, consecutive patients with peptic ulcer bleeding who underwent endoscopic hemostasis at our Hospital from January 2010 to December 2018 were enrolled. The relationship between rebleeding within 30 days after endoscopic hemostasis and the patients’ admission and endoscopic characteristics were analyzed using univariate and multivariate regression models. Results: Out of 274 patients with peptic ulcer bleeding, 17 (6.2%) patients experienced rebleeding. In the analysis of the patients’ admission characteristics, estimated glomerular filtration rate (eGFR) < 30 mL/min/1.73 m2 was an independent risk factor for rebleeding (odds ratio 4.77, 95% confidence interval 1.168-18.211, p = 0.03). Patients with eGFR < 15 mL/min/1.73 m2 with or without hemodialysis had the highest rebleeding rate at 36.8%. With respect to endoscopic characteristics, the rate of rebleeding was associated with combination therapy (p < 0.0001) and active bleeding (p = 0.03). Conclusion: Renal dysfunction might be an independent risk factor for rebleeding after endoscopic hemostasis in patients with peptic ulcer bleeding. Cite this article as: Ogiyama H, Tsutsui S, Murayama Y, et al. Renal dysfunction is an independent risk factor for rebleeding after endoscopic hemostasis in patients with peptic ulcer bleeding. Turk J Gastroenterol. 2021; 32(8): 622-630.